2016
DOI: 10.1111/cns.12555
|View full text |Cite
|
Sign up to set email alerts
|

7,8‐dihydroxyflavone Ameliorates Motor Deficits Via Suppressing α‐synuclein Expression and Oxidative Stress in the MPTP‐induced Mouse Model of Parkinson's Disease

Abstract: Taken together, these results indicate that DHF treatment may suppress the accumulation of α-synuclein and oxidative stress via activating TrkB and subsequently block the loss of dopaminergic neurons in the SN and striatum, thereby ameliorating MPTP-induced motor deficits in the C57BL/6 mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 46 publications
5
31
0
Order By: Relevance
“…Up until now, the behavioral assessments in the subacute MPTP mouse model are still controversial. Many studies have described motor defects [12][13][14] , while others have proven that the model hardly mimics the movement disorder of PD and may even induce hyperactivity in animals [10,15,16] . Here, in our research, subacute MPTP treatment failed to cause typical movement defects in spite of the serious damage to the dopaminergic neurons and the remarkable decrease in DA content.…”
Section: Discussionmentioning
confidence: 99%
“…Up until now, the behavioral assessments in the subacute MPTP mouse model are still controversial. Many studies have described motor defects [12][13][14] , while others have proven that the model hardly mimics the movement disorder of PD and may even induce hyperactivity in animals [10,15,16] . Here, in our research, subacute MPTP treatment failed to cause typical movement defects in spite of the serious damage to the dopaminergic neurons and the remarkable decrease in DA content.…”
Section: Discussionmentioning
confidence: 99%
“…In another related study using the fluid percussion injury (FPI) model, treatment with 7,8-DHF successfully restored TrkB signaling and memory function in the Barnes maze test [109]. 7,8-DHF also exhibited beneficial effects in the treatment of neurodegenerative diseases, including Alzheimer's disease (AD), Parkinson's disease (PD), Huntington's disease (HD), and amyotrophic lateral sclerosis (ALS) [110][111][112][113][114]. Recently, a derivative of 7,8-DHF, namely, BrAD-R13, was approved by the FDA for use in clinical trials for the treatment of mild to moderate AD.…”
Section: Improvement Of Bdnf Delivery and The Development Of New Trkbmentioning
confidence: 99%
“…Xiao-Huan Li et al reported a biological evaluation of DHF molecule that suppressed ASN expression and oxidative stress against MPTP induced Parkinson mice model 15 . The 7,8-Dihydroxyflavone (DHF) is a member of the flavonoid family, and highly present in vegetables and fruits.…”
mentioning
confidence: 99%